Correcting misperceptions of out-partisans decreases American legislators’ support for undemocratic practices - Druckman, James N.; Kang, Suji; Chu, James; N. Stagnaro, Michael; Voelkel, Jan G.; Mernyk, Joseph S.; Pink, Sophia L.; Redekopp, Chrystal; Rand, David G.; Willer, Robb (Proceedings of the National Academy of Sciences - PNAS, 2023)
There is substantial concern about democratic backsliding in the United States. Evidence includes notably high levels of animosity toward out-partisans and support for undemocratic practices (SUP) among the general public. Much less is known, however, about the views of elected officials—even though they influence democratic outcomes more directly. In a survey experiment conducted with state legislators ( N = 534), we show that these officials exhibit less animosity toward the other party, less SUP, and less support for partisan violence (SPV) than the general public. However, legislators vastly overestimate the levels of animosity, SUP, and SPV among voters from the other party (though not among voters from their own party). Further, those legislators randomly assigned to receive accurate information about the views of voters from the other party reported significantly lower SUP and marginally significantly lower partisan animosity toward the other party. This suggests that legislators’ democratic attitudes are causally linked to their perceptions of other-party voters’ democratic attitudes. Our findings highlight the importance of ensuring that office holders have access to reliable information about voters from both parties.